‘Sarimin’ Game Petualangan Adaptasi Webtoon Dengan Konsep Discovering The Mythical Creatures - Nugrahardi Ramadhani; Annisa Dhia Baswedan (Jurnal Bahasa Rupa, 2021)
This research focused on designing a webtoon adaptation game "Sarimin" based on Indonesian mythical creatures. The purpose of this paper is to introduce various Indonesian mythical creatures as the preservation and appreciation of local mythical culture from the positive side through the player's point of view as Sarimin, who is the personification of the white monkey djinn and the main character of the webtoon 'Sarimin'. The design methods used were literature study, observation of historical physical relics, experimental studies, interviews with game developers, prototyping, and testing. Based on the research results, the "Discovering The Mythical Creatures" design concept was created where players would explore the levels and be introduced to Indonesian mythical creatures and their stories related to the story from the webtoon 'Sarimin' with adventure-platformer gameplay.